THE ADEQUACY OF THE LATVIAN PENSION SYSTEM IN THE FACE OF EUROPEANIZATION - Dundure, Inara (European Scientific Journal, ESJ, 2014)
The aim of the paper is research and analyses of the dimensions of pension adequacy in Latvia and the deficiencies of the current social protection and old-age pensions in the light of the various European social models and their origins. In order to reduce poverty and social exclusion, in all European social models it is essential for the governments to take active part and support the basic elements - pensions, health and longterm care, social protection of the poor and the disabled, and tax redistribution. The task of each pension scheme is providing the contributor the possibility to maintain his/her standard of living also after retiring. By ensuring sufficient level of income replaceability, the risk of poverty among older people is minimized. Yet the comparatively new pension systems of the East- European countries, as well the pension system of Latvia, lack this ability. The analyses of the author highlight the need to review the design of the Latvian pension system and to find the right balance between PAYG (Pay-As-You-Go) systems and fully funded systems. In comparison with other European countries, the replacement ratio in Latvia is one of the lowest within the EU 27 countries. Other important vice of the Latvian pension system, which especially influences the income of single pensioners, is the inability to inherit the accumulated capital within the state obligatory funded pension scheme.